The influence of pavement–vehicle interaction on highway fuel consumption by field measurement - Jiao, Xin; Bienvenu, Michael (Transport, 2016)
Field experiments are performed in which Fuel Consumptions (FCs) are measured by operating passenger car over thirteen one-mile roadway sections at two highway speeds in Florida. The sections are composed of 6 flexible pavement sections and seven rigid pavement sections with varied pavement surface conditions and testing temperature. The first objective is to capture the fuel differences between flexible pavement and rigid pavement considering the effect of pavement roughness and pavement temperature. By ANalysis of COVAriance (ANCOVA), results show less fuel is consumed on rigid pavement opposed to flexible pavement by 2.25% at 93 km/h and 2.22% at 112 km/h. Fuel differences are found statistically significant at 95% Confidence Level (C.L.). Fuel savings on rigid pavement exhibits good agreement with authors’ Phase I direct comparison field study. Furthermore, fuel data from flexible pavement is applied to calibrate the Highway Development and Management IV (HDM-4) FC model in order to detect and quantify the impact of pavement deflection on FC. Calibrated models are evaluated and validated with experiment data. By results, the deflection-indhuced fuel effect is disclosed by the positive deflection adjustment coefficient generated from the calibration. It is also found that an increase of 0.1mm in pavement deflection at 25 °C (pavement temperature) would increase the FC by 1.53% at 93 km/h and 1.46% at 112 km/h. Results demonstrate good agreement with other findings.